PERILAKU MENJAGA KESEHATAN GIGI DAN MULUT PADA SANTRI PONDOK PESANTREN AL-AZHAR JEMBER - H, Hestieyonini; K, Kiswaluyo; E.Y., Ristya Widi; Meilawaty, Zahara (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Dental health perception and behavior of Indonesian people is still worse. The prevalence dental caries and oral diseases in Indonesia were increasing. A lot of Indonesia people didnât know about how to care oral health. The aim of this study was to know how to care dental health of student in Pondok Pesantren Al-Azhar Jember. This was descriptive study. Sampling technique was absolute technique and used questioner. Result analysis was showed in frequency distribution. The result showed that dental health care behavior of elementary students was good; otherwise junior high school students were moderate.